Design science in operations management: conceptual foundations and literature analysis - Dresch, Aline; Pacheco Lacerda, Daniel; Cauchick-Miguel, Paulo Augusto (Brazilian Journal of Operations & Production Management, 2019)
Goal: The aim of this paper is to show that design science and design science research may contribute as a methodological approach in the context of operations management. Design/methodology/approach: A systematic literature review was conducted to identify articles that have applied design science and design science research in operations management studies. Results: The findings show that the concepts of design science and design science research are relevant and can be applied to conduct more relevant research. Moreover, this paper presents appropriate steps for conducting design science research and provides a summary of the main studies conducted in operations management until the present time. Some drivers are also suggested for advancing research in design science and design science research in operations management. Limitations of the investigation: The main limitation of this paper is the lack of an empirical approach. Practical implication: This paper can contribute to other researchers in the sense of presenting a methodological approach that can help reducing the gap that exists between the research that is developed by academics and what is necessary to support practitioners in organizations, mainly in operations management problems. Originality/value: Publications that discuss research in the area of operations management generally consider the aims and practices determined by traditional sciences (natural and social) as a reference. Thus, it is important to explain the core concepts and foundations, as well as presenting the papers, which have already been developed using design science research in operations management, is necessary for advancing the discussion regarding the use of this method in this area.